A protocol for an individualised, facilitated and sustainable approach to implementing current evidence in preventing falls in residential aged care facilities - Haralambous, B.; Haines, T.; Hill, Keith; Moore, K.; Nitz, J.; Robinson, A. (BioMed Central Ltd, 2010)
Background. Falls are common adverse events in residential care facilities. Commonly reported figures indicate that at least 50% of residents fall in a 12 month period, and that this figure is substantially higher for residents with dementia. This paper reports the protocol of a project which aims to implement evidence based falls prevention strategies in nine residential aged care facilities (RACFs) in Australia. The facilities in the study include high and low care, small and large facilities, metropolitan and regional, facilities with a specific cultural focus, and target groups recognised as being more challenging to successful implementation of falls prevention practice (e.g. residents with dementia). Methods. The project will be conducted from November 2007-November 2009. The project will involve baseline scoping of existing falls rates and falls prevention activities in each facility, an action research process, interactive falls prevention training, individual falls risk assessments, provision of equipment and modifications, organisation based steering committees, and an economic evaluation. In each RACF, staff will be invited to join an action research group that will lead the process of developing and implementing interventions designed to facilitate an evidence based approach to falls management in their facility. In all RACFs a pre/post design will be adopted with a range of standardised measures utilised to determine the impact of the interventions. Discussion. The care gap in residential aged care that will be addressed through this project relates to the challenges in implementing best practice falls prevention actions despite the availability of best practice guidelines. There are numerous factors that may limit the uptake of best practice falls prevention guidelines in residential aged care facilities. A multi-factorial individualised (to the specific requirements of each facility) approach will be used to develop and implement an action plan in each participating facility based on the best available evidence. © 2010 Haralambous et al; licensee BioMed Central Ltd.